Exploring the implementation of smart technologies in the construction industry - Wee, Xin Rhu (2023)
As urbanisation continues to surge, the construction industry is grappled with an array of unprecedented economic, environmental, and social challenges. With a heightened awareness of these challenges, the construction industry is compelled to overhaul its current operations by incorporating smart technologies. In spite of this, there has been a paucity of research investigating about the application and adoption level of smart technologies, drivers as well as barriers of its adoption in Malaysian construction industry. As such, this study aims to uncover the potentials of incorporating smart technologies in the Malaysian construction industry. The objectives of this study are to determine the adoption level of smart technologies as well as drivers and challenges influencing its adoption. 10 types of smart technologies, 12 drivers and 13 challenges were identified from literature review. A quantitative approach was employed for this study, whereby online questionnaires were disseminated to the construction practitioners in Selangor and Wilayah Persekutuan Kuala Lumpur (WPKL). 175 responses were collected and analysed using Cronbach’s Alpha Reliability Test, Arithmetic Mean, Friedman Test, Spearman’s Correlation Test and Kruskal-Wallis Test. The findings revealed that Cloud Computing is highly adopted in Malaysia construction industry. Additionally, the study highlighted that organisational drivers are the primary impetus and economic challenges are the main hindrance to the successful implementation of smart technologies in their projects. Spearman’s Correlation test demonstrated that the major drivers and challenges influencing the adoption of smart technologies are associated with organisational aspects. Moreover, this study unveiled that respondents' prioritisation of drivers and challenges associated with the adoption of smart technologies varies based on their social demographics, which includes company business activities, organisational position, working experience and company size. The outcomes of this research serve as a guideline to the policymakers, government agencies, and professional bodies in devising a digital transformation roadmap for the Malaysian construction industry.